Masks in the Form of Memorization of the Qur'an: An Analysis of the Fatwa of Al-Lajnah Ad-Dāʽimah Li Al-Buhūṡ Al-ʿIlmiyyah wa Al-Iftā' Perspective of Norm Enhancement Theory - Muntaha, Ridwan; Ahda Sabila, Ahmad (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
The practice of handing over the mascot in the form of memorizing the Qur'an in a marriage contract has given rise to an interesting legal discourse in the realm of contemporary fiqh. One of the religious authorities that has responded to this phenomenon is Al-Lajnah Ad-Dāʽimah Li Al-Buhūṡ Al-ʿIlmiyyah wa Al-Iftā', a leading fatwa institution in Saudi Arabia. This study aims to examine in depth the fatwa issued by the institution regarding the validity of memorizing the Qur'an as a form of mascot, by tracing the basics of legal istinbāṭ, the relevance of the sharia postulates used, and the socio-religious context behind this view. The method used in this study is a qualitative approach with normative and descriptive analysis. This study concludes that the mascot in the form of memorization or teaching of the Qur'an is permissible in Islamic law, as affirmed in the fatwa of Al-Lajnah Ad-Dāʽimah number 6029. This fatwa allows the form of non-material mascot in conditions of financial incapacity. However, from the perspective  of ushul fiqh, the fatwa approach is considered too textual (monotext) and does not reflect the integration between partial postulates, general principles of sharia, and basic Islamic values. Thus, non-material monogamy such as the teaching of the Qur'an is not only legally valid, but also reflects the spirituality, simplicity, and principle of agreement in marriage, as long as it is understood within the framework of intact and contextual sharia norms.